Expanded Endoscopic Transsphenoidal Resection of Tuberculum Sella Meningioma Invading the Optic Canal - Klironomos, Georgios; Bruni, Margherita; Dehdashti, Amir R. (Journal of Neurological Surgery Part B: Skull Base, 2018)
A 61-year-old male patient presented with recurrent malignant meningioma involving the left optic canal and decreased vision from the left eye. The patient had undergone orbital exenteration on the right 2 years ago. The decision to treat the patient was made based on the significant vision deterioration and rapid tumor growth. Endoscopic transsphenoidal approach considered the most suitable route due to the inferomedial invasion of the optic canal. Gross total removal was achieved and the patient's vision improved postoperatively. The patient developed hydrocephalus 4 weeks postoperatively and cerebrospinal fluid (CSF) leak. Ventriculoperitoneal shunt placement corrected both hydrocephalus and CSF leak.The link to the video can be found at: https://youtu.be/2cOF0pf5gAk.
Keywords: expanded transsphenoidal; endoscopic; vision compromise; optic canal invasion